SOP Model Based on Employment Instruction from EMI Results to Improve the Satisfaction of Higher Education Service (Asian Education Studies, 2018)
This study aim for analyze satisfaction Higher education service which is a form of servant performed bymanagers to stakeholders, based on Internal Quality Evaluation (EMI) result, from EMI achievement, set theStandard Operational Procedure and Work Instruction model, given the satisfaction of service is a very importantpart. The research method is correlation with the indicator consist of standard of Content, Process, Competenceof graduates, Educator and educational staff, Facilities and infrastructure of Education, Management of Prodi,Financing, Assessment, Research and Community Service, then, from EMI standard, correlated withstakeholders' satisfaction, with satisfaction level determined by category (a) satisfactory, if Expected Service/ES= Perceived Service (PS), (b) is not satisfactory when perceived service is lower than expectation (ES ≥ PS) and(c) very satisfying/happy when the service is perceived to exceed expectations (PS≥ES), and then performed dataanalysis. To define the model using several stages of the 4-D model include stages, definitions, design,development, and use or application. The result of correlation on study program A and study program B andIslamic education are different, for study program A is Competency Standard of Graduates (X3) with regressioncoefficient b3 = 0,076 and correlation coefficient R3 = 0,186, while study program B is Graduate CompetencyStandard (X3) with regression coefficient b3 = 0,138 with correlation coefficient R3 = 0,183, while indicatoreducation according to government’s provision, which has correlation level at graduate level. The results of thisresearch become the basis in determining SOP Model and Work Instruction, which then tested at universitiesstudied, and in general the application of this model is in the category of Satisfactory.